Brain injury biomarkers as targets for drugs development and personalized treatment for traumatic brain injury patients - Sandler, Melissa; Almohaish, Sulaiman; Brophy, Gretchen M. (Frontiers in Pharmacology, 2025)
Drug treatment protocols for traumatic brain injury (TBI) that result in long-term, positive outcomes have yet to be determined for various reasons, including diversity of injury and difficulty in measuring outcomes. Brain injury biomarkers are increasingly being used for drug development and treatment research in patients with TBI to supplement pharmacokinetic studies, provide evidence of drug mechanism of action, detect early and long-term clinical outcomes, and homogenize study populations. The use of biomarkers to influence TBI drug development and treatment trials has the potential to lead to more innovative research and personalized patient care. Future TBI clinical trials that utilize these innovative biomarkers study designs and demonstrate strong correlations between biomarkers and clinical outcomes could permit shorter, less expensive, and more successful clinical trials.